Bacterial microbiome of lungs in COPD - Sin, Don; Sze, Marc; Hogg, James (International journal of chronic obstructive pulmonary disease, 2014)
Chronic obstructive pulmonary disease (COPD) is currently the third leading cause of death in the world. Although smoking is the main risk factor for this disease, only a minority of smokers develop COPD. Why this happens is largely unknown. Recent discoveries by the human microbiome project have shed new light on the importance and richness of the bacterial microbiota at different body sites in human beings. The microbiota plays a particularly important role in the development and functional integrity of the immune system. Shifts or perturbations in the microbiota can lead to disease. COPD is in part mediated by dysregulated immune responses to cigarette smoke and other environmental insults. Although traditionally the lung has been viewed as a sterile organ, by using highly sensitive genomic techniques, recent reports have identified diverse bacterial communities in the human lung that may change in COPD. This review summarizes the current knowledge concerning the lung microbiota in COPD and its potential implications for pathogenesis of the disease.